Continuum of HIV Care in Rural Mozambique: The Implications of HIV Testing Modality on Linkage and Retention. (15th August 2018) - Lopez-Varela, Elisa; Fuente-Soro, Laura; Augusto, Orvalho J.; Sacoor, Charfudin; Nhacolo, Ariel; Karajeanes, Esmeralda; Vaz, Paula; Naniche, Denise
Abstract : Introduction: Context-specific improvements in the continuum of HIV care are needed to achieve the UNAIDS target of 90-90-90. This study aimed to assess the linkage to and retention in HIV care according to different testing modalities in rural southern Mozambique. Methods: Adults newly diagnosed with HIV from voluntary counseling and testing, provider-initiated counseling and testing, and home-based HIV testing services were prospectively enrolled between 2014 and 2015 at the Manhiça District. Patients were passively followed up through chart examination. Tracing was performed at 12 months to ascertain causes of loss to follow-up. Fine and Gray competing risk analysis was performed to determine factors associated with the each step of the cascade. Results: Overall linkage to care as defined by having a CD4 count at 3 months was 43.7% [95% confidence interval (CI): 40.8 to 46.6] and 25.2% of all participants initiated antiretroviral therapy. Factors associated with increased linkage in multivariable analysis included testing at voluntary counseling and testing, older age, having been previously tested for HIV, owning a cell phone, presenting with WHO clinical stages III/IV, self-reported illness-associated disability in the previous month, and later calendar month of participant recruitment. Ascertaining deaths and transfers allowed for adjustment of the rate of 12-month retention in treatment from 75.6% (95% CI: 70.2 to 80.5) to 84.2% (95% CI: 79.2 to 88.5). Conclusions: Home-based HIV testing reached a sociodemographically distinct population from that of clinic-based testing modalities but low linkage to care points to a need for facilitated linkage interventions. Distinguishing between true treatment defaulting and other causes of loss to follow-up can significantly change indicators of retention in care. Abstract : Supplemental Digital Content is Available in the Text.